CASES IN RUSSIAN: EXPLANATION AND APPLICATION OF THE SIX CASES (NOMINATIVE, GENITIVE, DATIVE, ACCUSATIVE, INSTRUMENTAL, AND PREPOSITIONAL), THEIR ENDINGS, AND THEIR EFFECT ON SENTENCE STRUCTURE - Dzhurayeva Farakhbonu Ismatullayevna; Azamova daughter of Farzona Fazil; Andaqulova daughter of Iroda Akmal; Shamsiyeva daughter of Lola Salahuddin (European Science Publishing, 2024)
This article provides a detailed explanation of the six grammatical cases in the Russian language—nominative, genitive, dative, accusative, instrumental, and prepositional—highlighting their meanings, uses, and the grammatical endings that apply to nouns, pronouns, and adjectives in each case. It also explores how these cases influence Russian sentence structure, offering examples of how case endings shape the relationships between words and determine the syntactic role of each word in a sentence. By understanding these cases, learners can navigate Russian grammar more effectively and gain greater flexibility in sentence construction. The article emphasizes the importance of the case system in both syntax and meaning, making it essential for mastering Russian.
Keywords: Russian grammar, Nouns and pronouns, Grammatical cases, Nominative case, Genitive case, Dative case, Accusative case, Instrumental case, Prepositional case, Russian sentence structure, Syntax and word order, Case endings.